A 180nm CMOS Capacitorless Low Drop-Out Regulator for Battery-operated System - Pérez Bailón, Jorge; Calvo, Belén; Medrano, Nicolás; Martínez, Pedro A. (Jornada de Jóvenes Investigadores del I3A, 2017)
This paper presents a fully-integrated 180nm CMOS low drop-out regulator based on a simple telescopic cascode-compensated amplifier driving a PMOS pass-device. It provides a high precision 1.8V output voltage for battery voltages from 3.6V to 1.93V up to a 50mA load current with only 22μA quiescent current.